English unlimited. - Doff, Adrian (Cambridge University Press, 2011)
This book has practical CEF goals at the core of the course, every part of every unit contributes to achieving purposeful, real-life objectives. Across Cultures sections develop learners ntercultural competence as a fifth skill, and leading to more sensitive and more effective communication. Explore sections provide the extra ingredients for enhancing communicative ability.